Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus - Demite, Peterson R.; Cruz, Wilton P. Da; Bolton, Samuel; Moraes, Gilberto J. De (Zootaxa, 2018)
Until now, Honduriella Denmark & Evans has been known only from the holotype of its type species, Honduriella maxima Denmark & Evans. In recent surveys conducted in the Brazilian state of Amazonas, a second species of this genus was found. It is here described as Honduriella mcmurtryi Demite n. sp., based on morphological characteristics of adult females and males. Honduriella maxima is redescribed based on an examination of the holotype. In order to accommodate the new species, a modified characterisation of Honduriella is given.